Penguatan Perspektif Seks dan Gender dalam Implementasi Kebijakan Publik melalui Peran Pekerja Sosial - Abd. Naris Agam (MAN 4 Kota Pekanbaru, 2026)
This study examines social workers’ understanding of the concepts of sex and gender, their role in integrating gender perspectives into public policy implementation in the social sector, and the challenges and strategies for strengthening gender-responsive practice. The research uses a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving ten informants consisting of social workers, program coordinators, and community members involved in social service programs. Data were analyzed using an interactive model including data reduction, data display, and conclusion drawing. The findings show that social workers generally understand the distinction between sex and gender, although the depth of understanding varies. Social workers play important roles as facilitators, advocates, and agents of social change in promoting gender equality within public policy implementation. However, challenges remain, including limited gender awareness, strong patriarchal norms, and insufficient gender-related training. Strengthening gender perspectives requires capacity building, community empowerment, and stronger collaboration between government, social workers, and civil society. The study concludes that effective gender-responsive policy implementation depends on the active role of social workers at the community level.